Regional integration and food security in developing countries - Matthews, Alan (Food and Agriculture Organization of the United Nations, 2003)
Developing countries are active participants in the formation of regional trade arrangements (RTAs), but viewpoints differ on the desirability and on the efficient design of regional integration. The first objective of this paper is to review the regional integration debate for those involved in the preparation of food security strategies among developing countries. The paper concentrates primarily on the economic arguments while acknowledging that political motivations may often be the primary driving force behind RTAs. The second objective of the paper is to identify the potential role which regional integration arrangements might make to promoting food security among their members.
Keywords: Entwicklungsländer; Politik; Wirtschaftspolitik; Agriculture and state -- Developing countries; Food supply -- Government policy -- Developing countries; Trade blocs; Wirtschaftliche Integration; Ernährungssicherung; Developing countries -- Economic policy